1977
DOI: 10.1159/000152877
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Patterns in Thalassemia Intermedia (Constitutional Microcytic Anemia)

Abstract: Globin chain synthesis has been studied in 17 patients with thalassemia intermedia, and their relatives, also investigated by routine hematologic and hemoglobinic tests. The mean α/non α ratio was always around 2.20–2.30. In patients with severe thalassemia major, used as a control, the mean α/non a ratio was significantly higher, that is 3.11–3.07. Therefore, the hypothesis that the cause of the lesser severity of the thalassemia intermedia is a lesser imbalance of globin chain synthesis, is suggested. One or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
1

Year Published

1980
1980
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
2
6
1
Order By: Relevance
“…According to their biological fea tures, our 3 subjects with /¿Mhalassemia in termedia do not belong to either of these groups. They are more similar to some forms of thalassemia intermedia described in Italy [Bianco et al, 1977;Gallo el al., 1979], which is not unexpected since the family is of Italian origin.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…According to their biological fea tures, our 3 subjects with /¿Mhalassemia in termedia do not belong to either of these groups. They are more similar to some forms of thalassemia intermedia described in Italy [Bianco et al, 1977;Gallo el al., 1979], which is not unexpected since the family is of Italian origin.…”
Section: Discussionsupporting
confidence: 73%
“…The study of globin chain synthesis in several Italian families has indeed shown that one or both parents of subjects with thalassemia intermedia often have a mild picture of /Mhalassemia heterozygote, with a normal or subnormal non-«/« biosynthetic ratio [Bianco et al, 1977;Gallo et al, 1979]. Sometimes, the presence of genes for a-thalassemia together with homozygosity for /?-thalassemia lead to a clinical pattern of thalassemia intermedia [Bianco et al, 1977;Gallo et al, 1979].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the β-thalassemia intermedia patients had compound heterozygosity for IVSI-110 and IVSI-6 in our study, whereas the most frequently detected genotype among β-thalassemia intermedia patients was reported as IVSI-6/IVSI-6 in other studies [7, 8]. It is evident that the severity of the β-thalassemias is related to the degree of imbalance of the globin chains, and that thalassemia intermedia is caused by genes for β + -thalassemia, and thalassemia major is caused by genes for β-thalassemia [25]. It was reported that this may result from inheritance of a mild β-thalassemia mutation resulting in a residual β-chain output or reduction of α-chain synthesis due to co-inheritance of α-thalassemia or genetic interaction which results in increased synthesis of fetal hemoglobin [26].…”
Section: Discussionmentioning
confidence: 40%
“…This is the first report of the co-occurrence of Hb Camperdown and b°-thalassemia. b-thalassemia heterozygotes manifest a typical clinical picture, characterized by mild anemia, reduction in mean cell volumes and in mean cell hemoglobin concentrations, elevated concentrations of HbA 2 , altered erythrocyte morphology, and imbalance of globin-chain synthesis with an alpha/beta ratio > 1 (Bianco et al, 1977). Hb Camperdown is considered slightly unstable, resulting in a benign clinical course in heterozygous individuals (Wilkinson et al;1975;Blouquit et al, 1984;Kister et al, 1989;Miranda et al, 1996).…”
mentioning
confidence: 99%